Blocking TIGIT/CD155 signalling reverses CD8+ T cell exhaustion and enhances the antitumor activity in cervical cancer - Lu Liu; Aihong Wang; Xiaoli Liu; Sai Han; Yu Sun; Junhua Zhang; Lingyu Guo; Youzhong Zhang (Journal of Translational Medicine, 2022)
Abstract Objective TIGIT/CD155 has attracted widespread attention as a new immune checkpoint and a potential target for cancer immunotherapy. In our study, we evaluated the role of TIGIT/CD155 checkpoints in the progression of cervical cancer. Methods The expression of CD155 and TIGIT in cervical cancer tissues was detected using flow cytometry, immunohistochemistry (IHC) and gene expression profiling. In vivo and in vitro experiments have proven that blocking TIGIT/CD155 restores the ability of CD8+ T cells to produce cytokines. Changes in the NF-κB and ERK pathways were detected using western blotting (WB) after blocking TIGIT/CD155 signalling. Results TIGIT expression was elevated in patients with cervical cancer. High TIGIT expression in CD8+ T lymphocytes from patients with cervical cancer promotes the exhaustion of CD8+ T lymphocytes. In addition, CD155 is expressed at high levels in cervical cancer tissues and is negatively correlated with the level of infiltrating CD8+ T cells. We found that TIGIT, upon binding to CD155 and being phosphorylated, inhibited NF-κB and ERK activation by recruiting SHIP-1, resulting in the downregulation of cytokine production. Blocking TIGIT in activated CD8+ T cells attenuates the inhibitory effect of SHIP-1 on CD8+ T cells and enhances the activation of NF-κB and ERK. In vivo and in vitro experiments have proven that blocking TIGIT/CD155 restores the ability of CD8+ T cells to produce cytokines. Injecting the blocking antibody TIGIT in vivo inhibits tumour growth and enhances CD8+ T lymphocyte function. Treatment with a combination of TIGIT and PD-1 inhibitors further increases the efficacy of the TIGIT blocking antibody. Conclusions Our research shows that TIGIT/CD155 is a potential therapeutic target for cervical cancer.